PENGARUH KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Pelabuhan Indonesia III Persero Cabang Tanjung Perak Surabaya) - Ardilla Rizki Febriani, 09.05.51.0101 (Students Journal of Economic and Management, 2014)
This study aims to examine and analyze the effect of compensation, motivation, and work environment on the performance of employees of PT. Pelabuhan Indonesia (Persero) Branch Tanjung Perak Surabaya. Thi s research was conducted with a purposive sampling method and carried out at 56 employees PT.Pelabuhan Indonesia (Persero) Branch Tanjung Perak Surabaya. The test data used in this study include testing the validity of the product moment, with a Cronbach alpha reliability test, multiple linear regression analysis, and t test to test the hypothesis mebuktikan research, Test his research throughout the data is valid and reliable. The results of the analysis and discussion showed that: (1). Compensation has positive influence on employee performance, employee performance is also higher; (2). Motivation has a positive effect on employee performance, higher employee motivation, employee performance is also higher; (3). The work environment has a positive effect on employee performance, higher employee performance as well.Keywords: Compensation, Motivation, Work Environment, Employee Performance.